Bezpieczeństwo socjalne osób bezrobotnych w Polsce na tle sytuacji w Unii Europejskiej - Hajder, Krzysztof (Przegląd Strategiczny, 2014)
The social security of people affected by unemployment, and their families, is provided by various means of monetary instruments and support in kind. The fundamental element of social security, however, is a system of unemployment benefits. The literature of the subject presents contradictory opinions on the motivational function of benefits and their influence on unemployment levels. Advocates of neoclassical concepts stress the adverse influence of benefits on the level of unemployment and the time out of work. Representatives of Keynesian thinking point to the lack of a negative correlation between the level of benefits and the unemployment rate. Relative agreement between studies and opinions can be found in the observations and conclusions concerning the relation between the length of time on benefits and its adverse impact on re-entering employment. These conclusions find corroboration in the global statistics of Eurostat, detailed studies conducted in Germany and the Polish analysis of the implementation of the flexicurity model. The opposite conclusions can be drawn from the analysis of the Danish example, which shows that labor market stability can be maintained while providing some of the highest unemployment benefits in the world and a long period of providing them.